Facilitating Students' Cognitive Engagement in Online Asynchronous Discussion Within a Remote English Foreign Language Learning Environment - Maruanaya, Hendrik Jacob; Lekawael, Rosina F.J.; Loppies, Hellien Jequelin (KnE Social Sciences, 2024)
This study examined the cognitive presence of students in an asynchronous online discussion in the Second Language Acquisition (SLA) course. The course combined synchronous meetings through Zoom sessions to support student participation in asynchronous discussions. The study involved a cohort of 36 participants from the two remote extended campuses of Pattimura University in Maluku. Through content analysis, two key aspects were examined: (1) student participation rates, and (2) the extent of students’ cognitive presence within the discussions. The content analysis findings revealed that although each student made a minimum of two contributions per topic during online asynchronous discussions, they exhibited a moderately high level of cognition, incorporating problem recognition, exploration, integration, and solution, not only in individual messages but also in the overall exchange of information within the discussion thread. These findings suggest that a combination of synchronous meetings through Zoom sessions, tailored prompts, feedback, and social interactions enhances students' active engagement and utilization of cognitive skills in online asynchronous discussions. Keywords: online asynchronous discussion, English foreign language learning, cognitive presence